Validity, reliability, and responsiveness of the Brazilian version of the instrument World Health Organization Disability Assessment Schedule (WHODAS 2.0) for individuals with obstructive sleep apnoea - de Oliveira, Ana Cecília Silva; Zacarias, Laíla Cândida; de Souza, Clarice Cristina Cunha; Bezerra, João Paulo da Silva; Viana-Junior, Antônio Brazil; Sobreira-Neto, Manoel Alves; Leite, Camila Ferreira (Heart & lung, 2024)
•WHODAS 2.0 is a valid tool to assess functioning in subjects with OSA.•WHODAS is responsiveness to CPAP treatment.•The functioning of individuals with OSA is not associated with disease severity as classified by the apnoea-hypopnea index.•WHODAS can be a useful resource for the clinical assessment of patient functioning. Obstructive sleep apnoea (OSA) is a disabling health condition, and there is no disease-specific patient-reported outcome instrument to assess individuals with OSA. To evaluate the psychometric properties of the Brazilian version of the World Health Organization Disability Assessment Schedule (WHODAS 2.0) in individuals with OSA. One hundred individuals with OSA responded to the WHODAS 2.0 version of 36 items, the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index (PSQI), and the 12-item health survey (SF-12). Internal consistency, convergent and discriminative validity, and responsiveness to continuous positive airway pressure (CPAP) were the psychometric properties tested. Cronbach's α values indicate good internal consistency (0.91 – 0.73), except for the self-care domain (α = 0.52). Convergent validity indicated an excellent correlation (r = -0.80) between the domains of functioning and quality of life. Discriminative validity showed no association between OSA severity and functioning (p = 0.90). The responsiveness to CPAP treatment showed a large effect size (r = 0.82; p < 0.05) The WHODAS 2.0 instrument is valid, reliable, and responsive for assessing individuals with OSA.